2005
DOI: 10.7863/jum.2005.24.9.1205
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal Second-Trimester Ultrasonographic Visualization of the Fetal Heart in Obese Women

Abstract: Repeated ultrasound examination for SUV of the fetal heart at a later gestational age dramatically reduces SUV. However, obese patients continue to have much higher rates of persistent SUV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
4
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(94 citation statements)
references
References 13 publications
4
82
4
4
Order By: Relevance
“…26 The result obtained in the present study, showing poor correlation does matches with the similar study conducted on a Thai population on 32-35 weeks of gestational age.…”
Section: Discussionsupporting
confidence: 75%
“…26 The result obtained in the present study, showing poor correlation does matches with the similar study conducted on a Thai population on 32-35 weeks of gestational age.…”
Section: Discussionsupporting
confidence: 75%
“…14 A total of 300 pregnant women completed the study, 292 had both early and follow up anatomy scans while 8 cases with confirmed lethal anomalies by early scan chose to terminate their pregnancies and the anomalies were confirmed after termination. 15 The incidence of anomaly in our study was 3.67%. We found anomalies were more in advanced age group women in our study (p<0.001).…”
Section: 13mentioning
confidence: 77%
“…Maternal obesity is associated with less complete anatomical surveys, increased number of scans required, decreased detection of fetal anomalies and limitation of the visualization of the fetal organs Hendler 2005;Dashe 2009;Thornburg 2009;Aagaard-Tillery 2010;Maxwell 2010). The findings that are of importance for the parents are, of course, those indicating the presence of lethal anomalies and even other anomalies that have the potential for causing future severe handicap in the child.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…The need for continuous education is recognized as an important factor in ensuring effective screening that in principle is made possible by the improved resolution of the ultrasound image (Ogge 2006;McBrien 2010). The influence of obesity on diagnostic performance has not been studied extensively, but the rate of completed examinations was lower in the group with maternal obesity than in the other groups Hendler 2005;Thornburg 2009;Maxwell 2010). The influence of maternal obesity on ultrasound detection of fetal anomalies has been studied by Dashe et al (N=10,112) and Aagaard-Tillery et al (N=8,555) in two low-risk US populations (Dashe 2009;Aagaard-Tillery 2010).…”
Section: Factors Affecting the Performance Of Screeningmentioning
confidence: 99%